Comparative Evaluation of The Efficacy Of Rotary file system (Kedo-S) Vs Hand K-Files In Root Canal Preparation Of Primary Teeth Using Cone Beam Computed Tomography (CBCT) - An In Vitro Study - Abhinaya Srinivas; LGanesh Jeevanandan; Lavanya Govindaraju; Erulappan Muthu Ganapathi Subramanian (Brazilian Dental Science)
Objective: To evaluate the efficacy of rotary Kedo-S and hand K-files in shaping ability in primary canines using cone beam computed tomography. Materials and Methods: Thirty extracted primary maxillary and mandibular canines were selected. Using cone beam computed tomography the teeth were scanned before instrumentation. In Group I, the teeth were prepared using stainless steel K file up to the size of 40. In the Group II teeth, U1 size Kedo-S rotary file was used in crown down technique. The instrumented teeth were scanned again with cone beam computed tomography and the images were compared. Results: The canal taper was more conical for rotary Kedo-S files as compared to K-files, which was statistically significant. Conclusion:  Canal preparation with Rotary files resulted in more conical canals when compared to manual instrumentation in primary teeth that contributes to more uniform obturation.